Population Ecology of the Cooperatively Breeding Acorn Woodpecker. (MPB-24), Volume 24 - Koenig, Walter D.; Mumme, Ronald L. (Monographs in Population Biology Ser., 2020)
Ever since the acorn woodpecker was observed and described by Spanish explorers, its behavior--particularly the unique habit of caching acorns in specialized storage trees or granaries--has impressed observers. Acorn woodpeckers are also one of the few temperate zone species in which young are reared communally in family groups. This demographic study investigates the complexities of acorn storage and group living in acorn woodpeckers at Hastings Reservation in central coastal California. It is one of the most thorough studies of any avian social system to date.